A comparative study of adsorbents derived from coal fly ash for the adsorption of tetracycline from aqueous solutions - Tichapondwa, Shepherd Masimba (University of Pretoria, 2025)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2024.